Efficacy of adjuvant capecitabine in residual triple negative breast cancer: a multicenter observational Turkish Oncology Group (TOG) study - Tasci, Elif Senocak; Kutlu, Yasin; Olmez, Omer Fatih; Mutlu, Arda Ulas; Gundogdu, Yasemin; Seyyar, Mustafa; Yildiz, Ibrahim (Taylor & Francis Ltd, 2024)
BackgroundTriple negative breast cancer (TNBC) is characterized by high rates of recurrence, especially in patients with residual disease after neoadjuvant chemotherapy (NAC). Capecitabine is being used as standard adjuvant treatment in residual TNBC. We aimed to investigate the real-life data regarding the efficacy of capecitabine in residual TNBC.Design and methodsIn this retrospective multicenter study, TNBC patients with residual disease were evaluated. Patients, who received standard anthracycline and taxane-based NAC and adjuvant capecitabine were eligible. Overall survival (OS), disease free survival (DFS) and toxicity were analyzed.Results170 TNBC patients with residual disease were included. Of these, 62.9% were premenopausal. At the time of analysis, the recurrence rate was 30% and death rate was 18%. The 3-year DFS and OS were 66% and 74%, respectively. In patients treated with adjuvant capecitabine, residual node positive disease stood out as an independent predictor of DFS (p = 0.024) and OS (p = 0.032). Undergoing mastectomy and the presence of T2 residual tumor was independent predictors of DFS (p = 0.016) and OS (p = 0.006), respectively.ConclusionThe efficacy of capecitabine was found lower compared to previous studies. Selected patients may have further benefit from addition of capecitabine. The toxicity associated with capecitabine was found lower than anticipated.
Keywords: Capecitabine; breast cancer; residual tumor; triple negative; toxicity